1995
DOI: 10.3382/ps.0741636
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Full Feed and Early Feed Restriction on Broiler Performance, Abdominal Fat Level, Cellularity, and Fat Metabolism in Broiler Chickens

Abstract: Three hundred sixty Peterson x Arbor Acres chicks were fed two feed regimens to compare their effects on adipose cellularity, adipocyte lipolysis, hepatic glucose oxidation, adipocyte lipogenesis, bird performance, and abdominal fat level. Broilers in the first regimen had ad libitum access to feed throughout the 7-wk experiment, whereas broilers in the second regimen consumed feed at will throughout the experiment except that they were subjected to feed restriction (1.49 kcal/g BW2/3 daily) from 7 to 12 d of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
3
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 24 publications
4
18
3
2
Order By: Relevance
“…However, there are conflicting reports on this issue, since some studies extrapolated the event observed in 42-day-old chicks back to a state that may have be present at an earlier age. Looking at 42-day-old broilers, Zhong et al (1995) did not observe that feed restriction reduced the amount of abdominal fat cells. However, they reported that lipocytes had become smaller.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are conflicting reports on this issue, since some studies extrapolated the event observed in 42-day-old chicks back to a state that may have be present at an earlier age. Looking at 42-day-old broilers, Zhong et al (1995) did not observe that feed restriction reduced the amount of abdominal fat cells. However, they reported that lipocytes had become smaller.…”
Section: Discussionmentioning
confidence: 99%
“…Na maioria dos trabalhos, a eficiência alimentar foi incrementada durante o período de realimentação (Plavnik & Hurwitz, 1985;Fontana et al, 1992;Robinson et al, 1992;Zubair & Leeson, 1994;Palo et al, 1995;Zhong et al, 1995).…”
Section: Introductionunclassified
“…In avian species, the liver is the major site for lipogenesis and bone marrow, and adipose tissue and skin make minor contributions (Zhong et al, 1995). It has been reported that hepatic lipogenesis is highly responsive to nutrient changes in diets, the nutritional state of the bird as well as the amount and composition of feed consumed (Hillgartner et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Many investigators had attributed such results to lipogenic responses (Rosebrough et al, 1986), and control of hyperplasia and/or hypertrophy of adipocytes (Zhong et al, 1995;Zubair and Leeson, 1996). Metabolic programming may be defined as a physiological process whereby early adaptation to a nutritional stress permanently changes the physiology and metabolism of the organism and continues to be expressed even in the absence of the stress that initiates it (Lucas, 1998;Patel and Srinivasan, 2002).…”
Section: Introductionmentioning
confidence: 99%